Information Communication and Technology (ICT) Adoption in Asian Countries: An Empirical Evidence of Economic and Socio-Cultural Factors - Wahyu Apriyantopo; Atik Aprianingsih (Bina Nusantara University, 2020)
The research dealt with factors affected the different Information Communication and Technology (ICT) adoptionrate among Asian countries. The primary purpose was to examine the impact of national wealth and culture onthe behavioral adoption of ICT empirically among selected countries in Asia. Data were collected from the WorldBank, World Economic Forum, and Hofstede’s cultural dimension index. Statistical correlation and multipleregression were utilized to analyze the dataset, such as Gross Domestic Product (GDP) as a proxy for nationalwealth and Hofstede’s cultural dimension as a proxy for culture. The result shows a significant relationshipbetween GDP per capita and uncertainty avoidance on the national ICT adoption index. This finding contributesto improving the acknowledgment of the GDP and national culture as the antecedent of ICT adoption in the globalfield. Practically, the research updates the previous similar ones and proposes further empirical research to extendthe scope of analysis.